Ultimate Axial Strength of Concrete-Filled Double Skin Steel Tubular Column Sections - S. İpek; E. M. Güneyisi (Advances in Civil Engineering, 2019)
This study aims at proposing a new model for evaluating the ultimate axial strength of concrete-filled double skin steel tubular (CFDST) composite columns. For this, a total of 103 experimental data regarding the ultimate strength of CFDST columns under axial loading were collected from the previous studies in the literature. All CFDST columns consist of two steel tubes being outer and inner circular hollow section. The model presented herein was developed by using gene expression programming. For this, the yield strength, diameter, and thickness of both outer and inner steel tubes, the compressive strength of annulus concrete, the length of the specimen, and the ultimate axial strength of the columns were utilized as the parameters. Assessment of the obtained results indicated that the generated model had a good performance compared to the existing models by the previous researchers and the equations specified in the design codes. The high value of R2 and narrow ranged fluctuation of the estimation error for the ultimate axial strength of the CFDST columns were also achieved through the proposed model.